Guia de conduta em pré-natal : desenvolvimento de tecnologia em enfermagem à luz da CIPE - versão alfa - Martinho, Neudson Johnson (2005)
The obstetric nurse returns to the scenery of reproductive health with their responsibilities enlarged, as strategy proposed by the World Organization of Health - OMS, for the reduction of the maternal and perinatal mortality rates. This fact increases the demands of better professional qualification, so that the interventions implemented for the protection of women’s and children’s health are effective and efficacious. In this perspective, we developed this documental study, aiming to propose a guideline for the nurses’ clinical actions in prenatal consultations in the physiological dimension, subsidized in the International Classification for the Practice of Nursing-CIPE. It was developed at the Center of Natural Childbirth of the Center of Family Development - CEDEFAM/UFC, located in the city of Fortaleza-CE. The population was constituted of 253 records of pregnant women that attended the prenatal nursing consultation in the period between July 2003 and August 2004, and the sample was composed of 62 records selected at random. We used an instrument for data collection that contained the Nursing phenomena according to the CIPE - alpha version. The data were collected in the months of May and August 2004. We detected that the more prevalent phenomenon in the pregnant women were: intermittent sleep (56,5%); functional dyspnea (51,6%); edema (37,1%); orthopnea (35,5%) and constipation (32,2%). We carried out the tests of association qui-square and Firsher, but there was not association of the phenomenon among themselves, nor with the other variables of the study. The conduct guide’s development made it possible to verify that the construction of technologies is something accessible to Nursing and that the CIPE can contribute to a better organization of the nurse’s actions during prenatal period, starting from the answers of the pregnant women facing the physiological alterations caused by pregnancy